Relationship Between The Level Of Knowledge And The Support Of The Family To The Schizophrenia Patient In The Internament Health Center Of Liquiça, 2023. - M. Pires, Alexandra; dos Santos Ximenes, Herminia; Barreto, Meriana; Frutalegio da Costa Freitas, Aureo; Oqui, Maximiano; Martins Soares, Caitano (Jurnal Syntax Fusion, 2024)
Statistical data mentioned by the World Health Organization (WHO) in 2020 globally an estimated 379 million people are affected by mental disorders, there are 264 million people who suffer depression, 45 million people suffer from bipolar disorder, 50 million people suffer dementia and 20 million people of whom suffer from schizophrenia. According to data published by the Mental Health Program, Ministry of Health Timor-Leste in 2020 reported 2,015 patients with mental disturbance conducted regular treatment at Health Centers and Hospitals, the majority of women with 1,078 patients and 973 of men. According to the prevalence report by the Health Services of the Municipality of Liquiça in 2021, reported a total of 821 people (337 men, 484 women) were registered. With a total of 399 people who received treatment at the health facilities, consisting of 174 men and 225 of women. According to the data of mental disorders patients by the Liquiça Health Center in 2022 with total registered patients were 118 people composed 46 men and 72 women. Based on the results of the research of 44 respondents on the relationship between the level of knowledge and the support of the family to the schizophrenia patient, it shows that the level of knowledge (knowing and understanding) with the good category 15 (34.1%), sufficient 17 (38.6%) and menus 12 (27.3%). Moreover, the supports of the family with the category good 13 (30.0%), sufficient 20 (45.5%) and menus 11 (25.0%). There is a strong relationship between the level of knowledge and the support of the family to the schizophrenia patient with the result of the Spearman Rank statistical test with SPSS version 20.0 with the significant coefficient p=0.000 means menus of 0.05 with the strong correlation coefficient between the level of knowledge and support of the family with the value r=0.670 with a strong relationship.Knowledge level